2017
DOI: 10.1089/dna.2017.3808
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA HOXA11-AS Exerts Oncogenic Functions by Repressing p21 and miR-124 in Uveal Melanoma

Abstract: Long noncoding RNAs (lncRNAs) have been reported to play vital roles in various human cancers. The aim of this study was to explore the critical role of lncRNA HOXA11-AS in uveal melanoma (UM) progression. Briefly, we found that HOXA11-AS is overexpressed in UM tissues and cells; HOXA11-AS could regulate UM cell growth, invasion, and apoptosis. Mechanistically, RNA immunoprecipitation demonstrated that HOXA11-AS could simultaneously interact with enhancer of zeste homolog 2 (EZH2) to suppress its target p21 pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 30 publications
1
51
0
Order By: Relevance
“…Previous evidences have proved that lncRNA HOXA11‐AS expression was found to be overexpressed and played an oncogene in several tumours . Xu et al showed that HOXA11‐AS expression was up‐regulated in glioma cell lines and samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous evidences have proved that lncRNA HOXA11‐AS expression was found to be overexpressed and played an oncogene in several tumours . Xu et al showed that HOXA11‐AS expression was up‐regulated in glioma cell lines and samples.…”
Section: Discussionmentioning
confidence: 99%
“…The underlying mechanism by how HOXA11‐AS involved in HCC tumorigenesis still remains to be researched. Growing studies indicated that lncRNAs acted crucial roles in several biological processes by playing as ceRNAs (competing endogenous RNAs) or molecular sponges to modulate‐specific miRNAs . Previous study showed that HOXA11‐AS functions as an oncogenic gene which enhanced glioma cell metastasis and growth by inhibiting miR‐214‐3p/EZH2 expression .…”
Section: Discussionmentioning
confidence: 99%
“…HOXA11‐AS has been uncovered to be expressed at high levels in multiple human cancers, including hepatocellular carcinoma and uveal melanoma 18,19 . However, the expression status of HOXA11‐AS in PCa tissues and cells still needs detecting.…”
Section: Resultsmentioning
confidence: 99%
“…lncRNA PCA3 promotes PCa progression by targeting miR‐218‐5p/HMGB1 17 . lncRNA homeobox A11 antisense RNA (HOXA11‐AS) has been verified to elicit facilitating effect on the progression of many cancers 18,19 . However, the potential role of HOXA11‐AS in PCa remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…This malignancy can originate in the choroid (80%), ciliary body (12%) and iris (8%) [63]. Recent studies found that dysregulated lncRNAs were involved in the pathological development of UM, such as lncRNA-numb [64], PAUPAR [65], CANT1 [66], P2RX7-V3 [67], MALAT1 [68], RHPN1-AS1 [69], HOXA11-AS [70], PVT1 [71] and FTH1P3 [72]. Cheng et al found that the ectopic expression of hypermethylated in cancer 1 (HIC1) in UM could inhibit cell proliferation and invasion, and that this was down-regulated as a tumor suppressor in UM.…”
Section: Uveal Melanomamentioning
confidence: 99%